A new marine controlled‐source electromagnetic receiver with an acoustic telemetry modem and arm‐folding mechanism. (24th August 2015) - Kai, Chen; Wenbo, Wei; Ming, Deng; Zhongliang, Wu; Gang, Yu
ABSTRACT: We developed a new marine controlled‐source electromagnetic receiver for detecting methane hydrate zones and oil and gas reservoirs on the seafloor, which is not imaged well by seismic reflection surveys. To determine the seafloor structure, the electromagnetic receiver should have low noise, power consumption, clock drift error, and operating costs while being highly reliable. Because no suitable receiver was available in our laboratory, we developed a new marine controlled‐source electromagnetic receiver with these characteristics; the receiver is equipped with acoustic telemetry modem and an arm‐folding mechanism to facilitate deployment and recovering operations. To demonstrate the applicability of our new receiver, we carried out a field experiment offshore of Guangzhou in the South China Sea, where methane hydrates have been discovered. We successfully obtained controlled‐source electromagnetic data along a profile about 13 km long. All six new receivers were recovered, and high‐quality electromagnetic data were obtained. Relatively high apparent resistivity values were detected. The results of the offshore field experiment support the claim that the electromagnetic data obtained using the new receiver are of sufficient quality for the survey target.